PELATIHAN DAN PENDAMPINGAN MGMP GURU MATEMATIKA KABUPATEN SUKOHARJO DALAM PENGELOLAAN PEMBELAJARAN BERMUATAN ETHNOMATHEMATICS BERBASIS GOOGLE SITES - Toyib, Muhamad; Faiziyah, Nuqthy; Yuliana, Irma (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. The objective of this community service is twofold: (a) to provide junior high school teachers in Sukoharjo Regency with guidance on designing mathematics learning activities that incorporate ethnomathematics using Google Sites, and (b) to conduct workshops and training sessions for teachers to help them integrate ethnomathematics into their learning activities on Google Sites. The training is conducted offline in Sukoharjo with MGMP Mathematics partners. There were a total of 90 teachers from both public and private junior high schools in Sukoharjo who participated. This service activity is conducted through the subsequent phases: The preparation phase involves both internal and external coordination. The implementation stage focuses on introducing and training individuals in the development of ethnomathematics-based learning activities using Google Sites specifically developed for mathematics education. The instructors have received rigorous training in ethnomathematics and have gained new expertise in designing activities that incorporate this approach. They have also developed proficiency in using Google Sites as an educational tool in their classrooms. During the training sessions, the participants are actively and enthusiastically involved. Over 80% of the participants successfully created Google Sites that included educational activities related to ethnomathematics. Furthermore, there is a requirement for enhanced assimilation of cultural context in mathematics education, together with the provision of feedback. Abstrak. Pengabdian kepada masyarakat ini bertujuan untuk: (a) memperkenalkan cara mendesain aktivitas pembelajaran matematika bermuatan ethnomatematika berbasis Google Sites bagi guru SMP di Kabupaten Sukoharjo; (b) mengadakan workshop dan melatih guru dalam mendesain aktivitas pembelajaran bermuatan ethnomatematika dan mengintegrasikannya dalam Google Sites. Pelatihan dilakukan secara luring dengan mitra MGMP Matematika di Sukoharjo. Pesertanya adalah 90 guru dari SMP Negeri dan Swasta di Sukoharjo. Kegiatan pengabdian ini dilakukan melalui tahapan sebagai berikut: persiapan, terdiri dari koordinasi internal dan eksternal; tahap implementasi yang meliputi pengenalan dan pelatihan pengembangan aktivitas pembelajaran bermuatan ethnomatematika berbasis Google Sites yang dirancang dalam pembelajaran matematika. Para guru telah dilatih secara teknis dengan pengalaman baru merancang aktivitas bermuatan ethnomatematika dan mengembangkan Google Sites sebagai sarana pembelajaran di kelas mereka; peserta terlibat penuh selama pelatihan. Lebih dari 80% peserta mampu mengembangkan Google Sites yang memuat aktivitas pembelajaran dengan ethnomatematika. Selain itu, terdapat umpan balik dan kebutuhan untuk peningkatan integrasi konteks budaya dalam pembelajaran matematika.